1962
DOI: 10.1007/bf02633343
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of methyl linoleate and its thermal decomposition products

Abstract: Methyl linoleate was heated for 10 hrs. at 300~ in the absence of air and fractionated by alembic distillation and urea adduct-formation.Intestinal absorptions of the urea adduct-fornling monomeric nonadduct-forming nlonomeric, and dimeric fractions were determined. It was found that dimers were half as well absorbed as the monomers.When fed to rats, dimers were better accepted and exhibited some toxicity symptoms different from the nonadduct-fornling monomers. The dinlers caused diarrhea, irritability, and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Crampton et al (7,15), Kaunitz et al (8), and Perkins et al (9) showed that diets containing 12-20% dimers caused high mortality rates when fed to the rats. At 5-10% of the diet, dimers decreased growth rate and lowered food efficiencies (8,10,11). The high mortality of rats fed 12-20% dimers may have been caused mainly by malabsorption rather than the toxicity of the dimers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crampton et al (7,15), Kaunitz et al (8), and Perkins et al (9) showed that diets containing 12-20% dimers caused high mortality rates when fed to the rats. At 5-10% of the diet, dimers decreased growth rate and lowered food efficiencies (8,10,11). The high mortality of rats fed 12-20% dimers may have been caused mainly by malabsorption rather than the toxicity of the dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Nutritional studies (7)(8)(9)(10)(11)(12) conducted on the dimer and polymer fractions of heated fats showed in some cases that rats fed high levels of dimer concentrates or polymers exhibited adverse effects such as depressed growth, diarrhea, oily and matted coats, lower basal metabolism, lower body temperature, and higher mortality rate. Although the apparent digestibility of dimers had been shown to be between 30 and 70% (10,13,14), their absorption by the rat has been questioned (15)(16)(17). In the present study, nonlabeled and 14Cqabeled methyl esters of dimeric fatty acids were prepared, and the absorption and nutritional effects of these dimers in the rat were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, data concerning triacylglycerol oligomer digestibility are confusing. 14,15 Our group has found that true digestibility of the different thermoxidized compounds from the heated olive oil was 30-40%, whereas that of thermoxidized compounds from the unused oil was much higher (80%). 16 Moreover, the digestibility of nonoxidized triacylglycerols seems negatively affected by the presence of large amounts of thermoxidized compounds in palm olein and olive oil.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it appears that triacylglycerol monohydroperoxides are hydrolyzed by pancreatic lipase to almost the same degree as the original triacylglycerols (11,12). However, data concerning triacylglycerol oligomer digestibility are confusing (14,15).Studies on altered fat digestibility often use radiolabeled markers, which do not always have the same composition as the altered compounds present in heated or used frying fats. Moreover, these markers are potentially harmful and rather expensive.…”
mentioning
confidence: 99%
“…Moreover, it appears that triacylglycerol monohydroperoxides are hydrolyzed by pancreatic lipase to almost the same degree as the original triacylglycerols (11,12). However, data concerning triacylglycerol oligomer digestibility are confusing (14,15).…”
mentioning
confidence: 99%